2003
DOI: 10.1007/s00221-003-1531-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trans-bullar gentamicin treatment on guinea pig angular and linear vestibulo-ocular reflexes

Abstract: This study provides the first systematic examination of the effects of intratympanic gentamicin instillation on vestibulo-ocular responses of guinea pigs during both Earth-vertical yaw axis and off-vertical axis rotation. A scleral search coil was sutured to the right eye of pigmented female guinea pigs prior to trans-bullar instillation of a 0.2-ml bolus of either 20 mg/ml or 40 mg/ml of gentamicin (1) into the right middle ear (unilateral treatment groups) or (2) into both ears (bilateral treatment groups). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In OVAR, the linear stimulus intensity is modeled by g sin(θ), where theta is the tilt angle and g is gravitational acceleration (Hess and Dieringer, 1990), thus the linear acceleration vector increases as tilt increases. HEV modulation amplitude also displayed an increase with increasing frequency of rotation, consistent with OVAR findings in other mammalian studies (Darlot & Denise, 1988; Jones et al, 2003). The modulation of HEV in mice appear to be consistent with gaze stabilization “translational” otolith-ocular reflexes; while the modulation of vertical eye position appears consistent with “tilt” otolith-ocular reflexes (Angelaki & Hess, 1996).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In OVAR, the linear stimulus intensity is modeled by g sin(θ), where theta is the tilt angle and g is gravitational acceleration (Hess and Dieringer, 1990), thus the linear acceleration vector increases as tilt increases. HEV modulation amplitude also displayed an increase with increasing frequency of rotation, consistent with OVAR findings in other mammalian studies (Darlot & Denise, 1988; Jones et al, 2003). The modulation of HEV in mice appear to be consistent with gaze stabilization “translational” otolith-ocular reflexes; while the modulation of vertical eye position appears consistent with “tilt” otolith-ocular reflexes (Angelaki & Hess, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…While Casp3 −/− mice did not differ greatly from WT in HEV amplitude, surprisingly, Casp3 +/− mice had multiple elevated HEV amplitude responses compared to WT at frequencies ≥0.20 Hz. Decreased modulation of OVAR HEV amplitude has been demonstrated to occur with gentamicin-induced lesions to the otolith organs in guinea pigs, likely due to the loss of afferent input from type I hair cells (Jones et al, 2003). Conversely, increases in modulation of OVAR HEV amplitude have been observed in humans with advanced age (Furman & Redfern, 2001), as well as cerebellar dysfunction (Anastasopoulos et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1A, column 5), the degree of asymmetry is similar to that observed in animals that have one normal labyrinth and one gentamicin-treated labyrinth (Fig. 1A, column 2; also see (Jones et al 2003;Della Santina et al 2005c)). Since the latter animals represent our goal with a unilateral prosthesis (i.e., to restore one implanted labyrinth to near-normal function after bilateral vestibular sensory loss), we consider this degree of asymmetry acceptable.…”
Section: Asymmetry Of Responses To Unilateral Prosthetic Stimulationsupporting
confidence: 75%
“…Gentamicin delivered via this route diffuses to and sequesters within the neuroepithelia of the vestibular labyrinth, where it kills Type I hair cells and causes nearly all Type II hair cells to lose their mechanosensitivity. [43] We [44;45] and others [46] have shown that this results in a marked decrease in AVOR gain for rapid head rotations of direction and sense that normally excites the treated ear's SCCs.…”
Section: A Surgical Techniquesmentioning
confidence: 99%